2016
DOI: 10.1371/journal.ppat.1005881
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging of Influenza Infection of the Trachea Reveals Dynamic Regulation of CD8+ T Cell Motility by Antigen

Abstract: During a primary influenza infection, cytotoxic CD8+ T cells need to infiltrate the infected airways and engage virus-infected epithelial cells. The factors that regulate T cell motility in the infected airway tissue are not well known. To more precisely study T cell infiltration of the airways, we developed an experimental model system using the trachea as a site where live imaging can be performed. CD8+ T cell motility was dynamic with marked changes in motility on different days of the infection. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…While our early analysis of the cellular phenotype throughout infection suggested that elimination of neutrophils resulted in a delay in the CD8 + T cell response, rather than sustained impairment, we were interested to examine whether the behavior of the cells in vivo would show a similar delay and recovery. In our lab, we previously established a method of imaging virus-specific CD8 + T cells within the trachea[ 37 ]. We recognize that some differences in the kinetics of clearing the infection may result in differences from those observed in the lungs, however, it is known that the virus is cleared from the organ by day 9 in wild type mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While our early analysis of the cellular phenotype throughout infection suggested that elimination of neutrophils resulted in a delay in the CD8 + T cell response, rather than sustained impairment, we were interested to examine whether the behavior of the cells in vivo would show a similar delay and recovery. In our lab, we previously established a method of imaging virus-specific CD8 + T cells within the trachea[ 37 ]. We recognize that some differences in the kinetics of clearing the infection may result in differences from those observed in the lungs, however, it is known that the virus is cleared from the organ by day 9 in wild type mice.…”
Section: Resultsmentioning
confidence: 99%
“…Imaging was performed as described in Lambert-Emo, et al . [ 37 ]. Briefly, images were captured using an Olympus FV1000AOM-Multiphoton imaging system in combination with a Spectra-Physics MaiTai-HP Deep See fs Ti:Sa laser system in the University of Rochester Light Microscopy core.…”
Section: Methodsmentioning
confidence: 99%
“…T cell velocities increased with Ptx, and confinement decreased (Figure 1A-C; Supplemental Figure 1A-C). On day 9 when cell velocities normally increase markedly, but transiently [9] (Supplemental Movie S1), the effects of Ptx slowed the cells and decreased confinement, with the largest fold-changes observed. Overall, the effects of Ptx-mediated inhibition of signaling through GPCRs varies over the course of acute infection.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that the changes on day 9 were the result of a significant reduction in signals received from ABC as the virus is cleared [9]. To address this, we re-introduced antigen in the form of soluble SIINFEKL peptides on days 8 and 9.…”
Section: Resultsmentioning
confidence: 99%
“…These interactions along with chemokine signals on the endothelium cause the T cells to arrest and undergo transendothelial migration into the infected tissue. CD8 T cells migrate through the space between the blood vessel and airway epithelium and cross the basement membrane of the epithelium to reach the infected epithelial cells (Lambert Emo et al 2016). Mouse studies suggest the CD8 T cells must also have an encounter with APC within the tissue to be retained and exert effector functions (McGill et al 2008).…”
Section: Cd8 + T-cell Responses To Seasonal Influenza Infectionmentioning
confidence: 99%